De la imagen-transparente a la imagen-opaca. Hacia una taxonomía de la imagen fotográfica a partir de la filosofía de Gilles Deleuze - León, Alejandro (2016)
Deleuze’s work is certainly heterogeneous. Throughout his life he managedto deal with an amazing variety of subjects: history of philosophy, psychoanalysis, politics, literature, painting, cinema, among others. However, the author of A Thousand Plateaus did not address a particularly relevant area for the twentieth century configuration –photography. This absence is unsettling not only because of the cultural importance of photography, but also because his reflections concerning the concept of image are a recurrent theme throughout his work. This research will not seek to determine the reasons why Deleuze did not explore the field of photography, because we believe that a question like this is, to say the least, idle. On the contrary, we will try to prolong his reflections in order to unfold the intuitions found in his philosophy that may help us to address the issue of the photographic. In this sense, our objective will be to develop a taxonomy of the photographic image from the distinction of two main types: the transparent image and the opaque image.